Balancing health care education and patient care in the UK workplace: a realist synthesis. Issue 8 (20th April 2017) - Sholl, Sarah; Ajjawi, Rola; Allbutt, Helen; Butler, Jane; Jindal‐Snape, Divya; Morrison, Jill; Rees, Charlotte
Abstract : Context: Patient care activity has recently increased without a proportionate rise in workforce numbers, impacting negatively on health care workplace learning. Health care professionals are prepared in part by spending time in clinical practice, and for medical staff this constitutes a contribution to service. Although stakeholders have identified the balance between health care professional education and patient care as a key priority for medical education research, there have been very few reviews to date on this important topic. Methods: We conducted a realist synthesis of the UK literature from 1998 to answer two research questions. (1) What are the key workplace interventions designed to help achieve a balance between health care professional education and patient care delivery? (2) In what ways do interventions enable or inhibit this balance within the health care workplace, for whom and in what contexts? We followed Pawson's five stages of realist review: clarifying scope, searching for evidence, assessment of quality, data extraction and data synthesis. Results: The most common interventions identified for balancing health care professional education and patient care delivery were ward round teaching, protected learning time and continuous professional development. The most common positive outcomes were simultaneous improvements in learning and patient care or improved learning or improved patient care. The most common contexts in which interventions were effective were primary care, postgraduate trainee, nurse and allied health professional contexts. By far the most common mechanisms through which interventions worked were organisational funding, workload management and support. Conclusion: Our novel findings extend existing literature in this emerging area of health care education research. We provide recommendations for the development of educational policy and practice at the individual, interpersonal and organisational levels and call for more research using realist approaches to evaluate the increasing range of complex interventions to help balance health care professional education and patient care delivery.